GESTURE CONTROL MENGGUNAKAN METODE COMPLEMENTARY FILTER - Magsyar, Ahmad Fajar; Belutowe, Yohanes Suban; Katemba, Petrus (STIKOM Uyelindo Kupang, 2021)
This study will discuss the use of the Complementary Filter method in hardware development that use gyroscope and accelerometer sensors, in order to see the ability of the sensor to read movement and assess how effective it is when used under movements with varying levels of aggressiveness. The complementary filter is a method that as the name suggests is to filter input data taken from the gyroscope and accelerometer sensors, this method is able to take data from both sensors and combine them into a single data that is more accurate by ignoring the shortcomings and using the advantages of each sensors The device that will be used is the MPU6050 GY521, this is a device that has both the two sensors on a single PCB so it is easier and more efficient to use, it has 3 axes meaning that this device can read motion in 3-dimensional space, the microcontroller used is a a variant of Arduino with an ATmega processor. After doing the test it was found that the use of the complementary filter method will greatly help the accuracy of the data because the filtered data contains very small noise with a significant difference when compared to raw data without using the filtering method, but because delay still can happens, wich cannot be helped by using this filtering method, this device can only be used with certain levels of movement